HARLEY DAVIDSON MOTOR TO MAKE THE SITE USING MACROMEDIA DREAMWEAVER MX - Dessy Caprina; Linda Wahyu Widianti, SKom, MMSI (Jurnal Sistem Informasi, 2001)
Today technology is growing rapidly, where human needs information superhighway.Especially with the internet facility which began ogled as a media campaign that wasquite interesting.To the writer want to provide news and information about Harley-Davidson Motorcycleto the lovers of these products. The site is expected to provide convenience for people inneed of the kinds of Harley Davidson Motor without having to visit the Showroom. Andalso this site is created by using the Indonesian language so that the fan motors will bemore easily understood.